2017
DOI: 10.1186/s40409-017-0110-2
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-type phospholipase A2 inhibitors from snake blood

Abstract: It is of popular and scientific knowledge that toxins from snake venom (among them the PLA2 and myotoxins) are neutralized by various compounds, such as antibodies and proteins purified from animal blood. Venomous and nonvenomous snakes have PLA2 inhibitory proteins, called PLIs, in their blood serum. One hypothesis that could explain the presence of these PLIs in the serum of venomous snakes would be self-protection against the enzymes of their own venom, which eventually could reach the circulatory system. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 89 publications
1
7
0
Order By: Relevance
“…66,67 Moreover, PLA2 inhibitors found in snake blood contain a region with high similarity to the carbohydrate recognition domain of C-type lectins. 68,69 Thus, our results suggest that the interaction between PLA2 and lectins could be specific; however, further experiments would be necessary to confirm this finding.…”
Section: Glycoproteomic Analysis Of B Alcatraz Venomsupporting
confidence: 60%
See 1 more Smart Citation
“…66,67 Moreover, PLA2 inhibitors found in snake blood contain a region with high similarity to the carbohydrate recognition domain of C-type lectins. 68,69 Thus, our results suggest that the interaction between PLA2 and lectins could be specific; however, further experiments would be necessary to confirm this finding.…”
Section: Glycoproteomic Analysis Of B Alcatraz Venomsupporting
confidence: 60%
“…The application of lectin-affinity chromatography for glycoproteome profiling is not a straightforward approach, and, in the case of Bothrops venoms, it may result in the binding of nonglycosylated proteins to the resin due to a possible unspecific interaction mediated by lectin regions outside the carbohydrate recognition domain . Nevertheless, in the case of PLA2s, previous studies showed the interaction of lectins and members of this toxin class. Interestingly, mammalian-secreted PLA2s are also recognized by receptors that contain C-type lectin domains. , Moreover, PLA2 inhibitors found in snake blood contain a region with high similarity to the carbohydrate recognition domain of C-type lectins. , Thus, our results suggest that the interaction between PLA2 and lectins could be specific; however, further experiments would be necessary to confirm this finding.…”
Section: Resultsmentioning
confidence: 88%
“…Many venomous snakes are known to have inhibitory proteins in their circulatory systems that can act as direct antagonists to their own venom components ( Mackessey 2010 ; Santos-Filho and Santos 2017 ). It is possible that the double-headed protease inhibitor found in B. brevicauda ’s submaxillary gland serves a similar function.…”
Section: Discussionmentioning
confidence: 99%
“…Available literature reports that the blood plasma of numerous snake species are naturally composed of endogenous phospholipase A 2 inhibitors, generally known as snake blood phospholipase A 2 inhibitors (sbPLIs). Primarily, they neutralize deleterious effects of phospholipase A 2 [ 82 , 83 ]. It implies that sbPLIs exert self-protection role against the enzymes of their own venom, which eventually reach the circulatory system [ 82 , 83 ].…”
Section: Snake Venom Phospholipase a 2 Inhibitormentioning
confidence: 99%
“…Primarily, they neutralize deleterious effects of phospholipase A 2 [ 82 , 83 ]. It implies that sbPLIs exert self-protection role against the enzymes of their own venom, which eventually reach the circulatory system [ 82 , 83 ]. What seems new is the fact that phospholipase A 2 inhibitory protein was detected in the venom, revealing that the protein is not only expressed in the snake blood serum.…”
Section: Snake Venom Phospholipase a 2 Inhibitormentioning
confidence: 99%